(3GdMGhjs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3jHJOF HHbjg GdHGH GdQGHY YTQ HYO GdHSdeI CQjfG (B( (3CNHQfG(B) (3SjS ddTYjQI hGdHQO YLjH cfOQ ef LQGf s
(3BNQgG (B:s
(3hjfJgi HGdHGH GdSGHY hGdYTQjf ai GdChQGe hYQYQ HGdSeGb ai GdMd HCPf Gddg JYGdi YR hLd Je GdLRA GdKGfi ef cJGH GdMGhi , hGdMeO ddg QH GdYGdejf s
(3GdLRA GdKGfis
(3HHbjI GdHGH GdQGHY YTQs
(3HBNQg agQS eaUd HGdeMJhjGJs
(3fSNI QGHYI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B69 s
Keywords: (3GdWHs